The role of astrocytes in ischemic stroke - mechanisms, functions and treatment - Wang, Yunlong; Wang, Ding; Li, Dongyu; Ma, Yuewen (Frontiers in Cell and Developmental Biology, 2025)
Ischemic stroke, characterized by localized cerebral hypoperfusion due to various etiologies, exhibits high global incidence and mortality rates. Astrocytes, as key structural and functional components of the neurovascular unit, play a critical role in maintaining homeostasis in the central nervous system. Following ischemic stroke, astrocytes undergo activation and adopt a distinct phenotype known as reactive astrocytes, which exert complex and dual roles in the pathological process. Upon ischemic injury, astrocyte activation often exacerbates damage and impairs functional recovery; however, it can also confer neuroprotection by shielding neurons from injury and releasing trophic factors to facilitate repair. Importantly, due to the intricate cascade of events and mechanisms involved after ischemic stroke, the precise role of astrocytes remains challenging to definitively elucidate. Nonetheless, astrocytes represent a pivotal target for therapeutic interventions in ischemic stroke. Herein, we review the activation of astrocytes following ischemic stroke, focusing on the intrinsic molecular mechanisms and functional implications of astrocyte reactivity. Additionally, we discuss the potential of combining rehabilitation technologies to enhance drug delivery and therapeutic efficacy, offering a promising strategy for the treatment of ischemic stroke.